Community College Environment - Neglected Research in Canada - Johnston, E. F. (Canadian Journal of Counselling and Psychotherapy, 1972)
Research has suggested the importance of institutional environment on the development of college students. This paper discusses the nature of such research in higher education and more specifically community colleges.Supporting a plea for more research in the assessment of college environments in Canada, major environmental measurement instruments are reviewed in detail showing the relationship of the various techniques.In order to encourage more research in this domain, educational and methodological implications of pursuing this research in Canada are discussed.